Alkali Metal Effects in Trans-Metal-Trapping (TMT): Comparing LiTMP with NaTMP in Cooperative MTMP/Ga(CH2SiMe3)3 Metalation Reactions - McLellan, Ross; Uzelac, Marina; Bole, Leonie J.; Gil-Negrete, Jose María; Armstrong, David R.; Kennedy, Alan R.; Mulvey, Robert E.; Hevia, Eva (Synthesis, 2019)
Stepwise metalation and trapping, so called trans-metal-trapping (TMT), of anisole is studied using LiTMP as base and Ga(CH2SiMe3)3 as trap. The isolated ‘trapped’ intermediate is also assessed in C–C bond forming reactions, highlighting the inherent advantages and remaining challenges of this system. The same base trap mixture is found to metallate N–Me bonds of the diamines TMEDA and PMDETA. Comparative studies replacing LiTMP by NaTMP have found significant alkali metal effects on the extent of both base-trap cocomplexation and onward reactivities of TMT products.
Keywords: metalation; gallium trans-metal-trapping; carbanions; cooperative effects; lithium; sodium